2017
DOI: 10.1097/md.0000000000006317
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and clinical features of adult atopic dermatitis in tertiary hospitals of China

Abstract: The prevalence of atopic dermatitis (AD) has increased substantially. Previous studies have focused mostly on pediatric patients, while epidemiological investigation on adult AD has been very limited.The aim of this study was to determine the prevalence and clinical features of adult AD in outpatients with dermatitis and eczema in China mainland.A multicenter cross-sectional study was conducted among outpatients with eczema or dermatitis from 39 tertiary hospitals of 15 provinces in China from July 1 to Septem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
36
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 24 publications
(25 reference statements)
2
36
0
2
Order By: Relevance
“…Our findings are in line with previous studies considering AD manifestations, as pruritus, erythema and dry skin were reported by most patients [1,30,38]. A slight variance was found between patients who reported pruritus (55.1% in first visit; 41.7% in last visit) and dry skin (48.7% in first visit; 43.3% in last visit).…”
Section: Discussionsupporting
confidence: 92%
“…Our findings are in line with previous studies considering AD manifestations, as pruritus, erythema and dry skin were reported by most patients [1,30,38]. A slight variance was found between patients who reported pruritus (55.1% in first visit; 41.7% in last visit) and dry skin (48.7% in first visit; 43.3% in last visit).…”
Section: Discussionsupporting
confidence: 92%
“…Thus, it is possible that pre‐existing ocular disorders and a dupilumab–AD disease‐specific interaction may be responsible for this increased incidence in dupilumab‐treated patients with AD, particularly as conjunctivitis was not associated with dupilumab in trials in other type 2 diseases . Allergic conjunctivitis is a common comorbidity in asthma and allergic rhinitis, as well as in AD . Both lesional and nonlesional skin in AD are characterized by epithelial barrier dysfunction, including abnormalities in keratinocyte terminal differentiation, keratinocyte lipid production and tight junctions, which all contribute to increased transepidermal water loss .…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of ophthalmic complications increases with AD severity . Allergic conjunctivitis and other ocular surface disorders are also common comorbidities of other atopic disorders such as asthma and allergic rhinitis …”
mentioning
confidence: 99%
“…Although it appeared to plateau at 10-20% in many developed countries, the incidence continues to increase in many developing countries (2). The prevalence of AD in adults is reportedly approximately 10% according to United States (US) population-based studies (4), and ranges from 1.8% to 4.6% according to several Asian population-based studies (5)(6)(7)(8). With an increasing prevalence in developing countries, and as one of the most common chronic diseases in developed countries, AD is currently considered a global public health concern.…”
mentioning
confidence: 99%